Finding the best promotional strategy for influencing the purchase of instant coffee by shoppers, A case study on Nestle Bangladesh Limited. - Arafath, Nafiz Akter (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.